Practical Wisdom: Management's No Longer Forgotten Virtue - Bachmann, Claudius; Habisch, André; Dierksmeier, Claus (Journal of business ethics, 2018)
The ancient virtue of practical wisdom has lately been enjoying a remarkable renaissance in management literature. The purpose of this article is to add clarity and bring synergy to the interdisciplinary debate. In a review of the wide-ranging field of the existing literature from a philosophical, theological, psychological, and managerial perspective, we show that, although different in terms of approach, methodologies, and justification, the distinct traditions of research on practical wisdom can indeed complement one another. We suggest a conciliatory conception of the various features of practical wisdom in management. This we take as a point of departure for a discussion of the significant implications of the subject for the theory and practice of management and for the direction of further research in the field.